Impact of coronary revascularization on coronary flow capacity measured by transthoracic Doppler echocardiography in patients with chronic coronary syndrome - Hiroki Ueno; Eisuke Usui; Masahiro Hoshino; Yoshihisa Kanaji; Tomoyo Sugiyama; Masahiro Hada; Tatsuhiro Nagamine; Yoshihiro Hanyu; Kai Nogami; Mirei Setoguchi; Kodai Sayama; Tomohiro Tahara; et al. (Scientific Reports)
Abstract Coronary flow capacity (CFC) integrates quantitative assessment of hyperemic myocardial blood flow and coronary flow reserve. We aimed to evaluate the effect of elective percutaneous coronary revascularization (PCI) on CFC using serial stress transthoracic Doppler echocardiography (STDE). Overall, 148 stable patients underwent STDE of the left anterior descending arteries (LAD), before and after elective PCI. Coronary flow velocity reserve (CFVR) was measured using basal and hyperemic diastolic peak velocity (hDPV). Vessels were classified into four CFC categories: severely, moderately, or mildly reduced CFC, and normal flow. Changes in hDPV and CFC status post-PCI, as well as predictors of hDPV increase, were assessed. Despite improvements in fractional flow reserve (FFR) in all cases, 31 cases (20.9%) showed a decrease in hDPV following PCI. Vessels with ischemic CFC, defined as moderately or severely reduced CFC, decreased from 46.6% (69/148) to 19.6% (29/148) post-PCI. Conversely, CFC worsened in 15.5% of patients. Multivariable analysis showed lower pre-PCI hDPV and ischemic CFC were independently predictive of higher-level (> 50%) hDPV increase after PCI. Approximately 20% of FFR-guided LAD PCI resulted in decreased hDPV. CFC deterioration was not uncommon despite FFR improvement. Preprocedural non-invasive STDE may help identify lesions that benefit from revascularization.